Improving Pregnant Mothers’ Intention toward HIV Testing through Home-based HIV Test and Education (HOPE) in Jember, Indonesia - Azkiel Fikrie; Ahmad Rifai; Dicky Endrian Kurniawan (Faculty of Nursing, Universitas Jember, 2021)
The HIV testing program's implementation among pregnant mothers is still not going well due to their intention. Their intention is needed because it can affect pregnant mothers' behavior toward HIV testing. New interventions are needed to solve this problem, such as Home-based HIV Test and Education (HOPE). This study aimed to analyze the influence of HOPE to improve HIV testing intention among pregnant mothers. The pre-experimental design was used with one group pretest-posttest approach—thirty pregnant mothers in Jember following this study and involved by using a purposive sampling technique. The data were collected by using the intention questionnaire and analyzed with the Wilcoxon test. The result showed that pregnant mothers' intention of HIV testing numbers increased from 20 to 27. The results indicate that there is a significant influence of HOPE on the intention of HIV testing in pregnant women (p = 0.033). The Home-based HIV Test and Education (HOPE) intervention can improve pregnant mothers' intention toward HIV testing. The HOPE intervention can reach all pregnant mothers (and their husbands) to discover HIV testing information. Involving their husbands on HOPE intervention encouraged pregnant mothers' intention of HIV testing because their husbands were decision-makers in their family, and pregnant mothers will take HIV testing.